THE MAIN DEVICES FOR GENERATING AND PROCESSING MICROWAVE SIGNALS AND FIELDS (American Journal of Research in Humanities and Social Sciences, 2025)
The article presents microwave devices used in non-destructive testing. They are built on the basis of waveguides, which is typical for the three-centimeter and eight-millimeter microwave ranges.